Privatization and strategic monitoring with gaussian priors - (:unkn) unknown (My University, 2005)
This article describes the sale and optimal regulation of a sequence of public utilities, where monitoring of regulatory compliance is costly. The government is concerned with the revenue raised by successive privatizations as well as the standard objective of efficiency in production. The costs of monitoring are private information to the government. At each stage in the sequence of privatizations, the public Bayes updates its distribution of posterior beliefs over the government's regulatory enforcement strategy. The government knows that this "learning " is taking place and chooses the time path of monitoring levels accordingly. © 2005 Sage Publications.
Keywords: Monitoring; Privatization; Regulation